The mystique of service and ethical commitment as the foundation of UMCH's social responsibility - Aguirre Garayar, Mónica (2020)
The article is the result of a presentation as part of a round table called: "Responsibility at the University", organized by the II International Seminar whose motto was "Impact of scientific research on society". Its objective is to generate a critical reflection on the fundamentals of the RSU, since in order to speak of the impact of an action it is convenient to reflect on what originates supports or triggers it. It contemplates the revision of the state of the art on the subject in refereed publications; questions various approaches generated around the subject in the academic and educational environment. It proposes, as the center of the RSU, the value of the human person from which the mystique of service and ethical commitment becomes; values ​​espoused by this University and, finally, it shares the experience of social responsibility that this House of Studies has, since its creation, as a consequence of an ethical commitment that promotes human and sustainable development.